PENERAPAN KONSELING KELOMPOK BERBASIS COGNITIVE RESTRUCTURING TERHADAP PENINGKATAN CITRA TUBUH POSITIF MAHASISWI UNIVERSITAS PGRI BANYUWANGI - Rizqi Amalia Putri (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
The high number of female students with low body image has affected their self-confidence, made it difficult for them to accept themselves, and often led them to compare themselves with others. Cognitive restructuring was chosen as a method to help these students by reshaping their negative thought patterns into more positive views about their bodies. This study aims to examine the effectiveness of group counseling using cognitive restructuring techniques in improving positive body image among 2024 cohort female students at Universitas PGRI Banyuwangi. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The subjects were eight female students with low body image, divided into two groups: four in the experimental group who received cognitive restructuring counseling, and four in the control group who received Person-Centered Therapy (PCT). The instrument used was a body image questionnaire based on the Multidimensional Body-Self Relations Questionnaire—Appearance Scales (MBSRQ-AS), which had been tested for validity and reliability. The hypothesis testing results, using paired sample t-tests and independent sample t-tests, showed a significance value (2-tailed) of 0.01 < 0.05, indicating that group counseling using cognitive restructuring techniques was effective in enhancing the positive body image of female students